Word of Mouth, Advertising on Brand Awareness, Brand Attitude and Purchase Decision on Prulink Product - Kadek Kusuma Dewi (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThe object of this research is the Word of Mouth, Advertising with Brand Awareness and Brand Attitude as a mediating variable in determining the purchase decision. This study aims to determine the direct influence of the Word of Mouth Advertising, Brand Awareness, Brand Attitude and Purchase Decision. From the results of this study showed 9 hypothesis that has been tested on 150 respondents were chosen by taking technique accidental sampling. Data were collected using a questionnaire and the analysis method used is the analysis of structural equation modeling. The results of this analysis indicate that word of mouth, advertising, brand awareness, brand attitude had a significantly direct effect on the purchase decision and also for the mediating role of brand awareness and brand attitude can strengthen relationships word of mouth and advertising appeal to the purchase decision. Accordingly, it is recommended that companies should attempt to create positive image about their product in the minds of their customers. Future study should be focused on ways and methods to explore in other contexts.